Spatial convergence and influencing factors of green total factor productivity of China’s urban agglomerations - Mao, Jinhuang; Yu, Zhi; Wang, Yifan; Wang, Lintao; Wang, Meimei (Frontiers in Environmental Science, 2023)
The article evaluates and analyzes the dynamic evolution, convergence mechanism and influencing factors of Green Total Factor Productivity (GTFP) growth in 19 urban agglomerations from both time and space dimensions using the SBM-GML model method, so as to provide a reference for decision making to comprehensively promote regional synergistic development strategy. The study finds that the eastern urban agglomerations show better competitiveness of green development and convergence rate of GTFP growth space than other regions, and even show synergistic development. Industrial structure and the level of financial services have a positive effect on green total factor productivity growth in urban agglomerations, while the business environment and the level of capital deepening have a negative effect.